Learning Methods for Islamic Religious Education for Mentally Disabled Children at SDLB Pertiwi Ponorogo - Endarwati, Rulik (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
Children with mental retardation are among children with special needs who need to get special treatment or certain methodologies, especially in Islamic religious education. So far, the government and society have not paid much attention to the learning methodology for mentally retarded children. The purpose of this study is to describe learning behavior, analyze learning methodologies and learning outcomes for mentally retarded children at SDLB Pertiwi Ponorogo. In this qualitative research, field conditions are described inductively through an Islamic religious education approach. Interviews, observations and document analysis were used for data collection. As a result, the method used in the learning process of Islamic religious education at SDLB Pertiwi Ponorogo is that the teacher conveys the material according to the conditions and abilities of the child by using simple language that is easily understood by mentally retarded children, and the methods used are still traditional, among others: the method demonstration, lecture method, question and answer method, assignment method and practice or drill method. From the several methods used, it can be seen that the learning outcomes for mentally retarded children are still very low even though the delivery is done repeatedly in language that is easily understood by mentally retarded children.